Different mutations in PDE4D associated with developmental disorders with mirror phenotypes. Issue 1 (7th November 2013) - Lindstrand, Anna; Grigelioniene, Giedre; Nilsson, Daniel; Pettersson, Maria; Hofmeister, Wolfgang; Anderlid, Britt-Marie; Kant, Sarina G.; Ruivenkamp, Claudia A L; Gustavsson, Peter; Valta, Helena; Geiberger, Stefan; Topa, Alexandra; et al.
Abstract : Background: Point mutations in PDE4D have been recently linked to acrodysostosis, an autosomal dominant disorder with skeletal dysplasia, severe brachydactyly, midfacial hypoplasia and intellectual disability. The purpose of the present study was to investigate clinical and cellular implications of different types of mutations in the PDE4D gene. Methods: We studied five acrodysostosis patients and three patients with gene dose imbalances involving PDE4D clinically and by whole exome sequencing, Sanger sequencing and array comparative hybridisation. To evaluate the functional consequences of the PDE4D changes, we used overexpression of mutated human PDE4D message and morpholino-based suppression of pde4d in zebrafish. Results: We identified three novel and two previously described PDE4D point mutations in the acrodysostosis patients and two deletions and one duplication involving PDE4D in three patients suffering from an intellectual disability syndrome with low body mass index, long fingers, toes and arms, prominent nose and small chin. When comparing symptoms in patients with missense mutations and gene dose imbalances involving PDE4D, a mirror phenotype was observed. By comparing overexpression of human mutated transcripts with pde4d knockdown in zebrafish embryos, we could successfully assay the pathogenicity of the mutations. Conclusions: Our findings indicate that haploinsufficiency of PDE4D results in a novel intellectual disability syndrome, the 5q12.1-haploinsufficiency syndrome, with several opposing features compared with acrodysostosis that is caused by dominant negative mutations. In addition, our results expand the spectrum of PDE4D mutations underlying acrodysostosis and indicate that, in contrast to previous reports, patients with PDE4D mutations may have significant hormone resistance with consequent endocrine abnormalities.